Decadally Resolved Lateglacial Radiocarbon Evidence from New Zealand Kauri. Issue 4 (24th October 2016) - Hogg, Alan; Southon, John; Turney, Chris; Palmer, Jonathan; Ramsey, Christopher Bronk; Fenwick, Pavla; Boswijk, Gretel; Büntgen, Ulf; Friedrich, Michael; Helle, Gerhard; Hughen, Konrad; Jones, Richard; et al.
Abstract: The Last Glacial–Interglacial Transition (LGIT; 15, 000–11, 000 cal BP) was characterized by complex spatiotemporal patterns of climate change, with numerous studies requiring accurate chronological control to decipher leads from lags in global paleoclimatic, paleoenvironmental, and archaeological records. However, close scrutiny of the few available tree-ring chronologies and radiocarbon-dated sequences composing the IntCal13 14 C calibration curve indicates significant weakness in 14 C calibration across key periods of the LGIT. Here, we present a decadally resolved atmospheric 14 C record derived from New Zealand kauri spanning the Lateglacial from ~13, 100–11, 365 cal BP. Two floating kauri 14 C time series, curve-matched to IntCal13, serve as a 14 C backbone through the Younger Dryas. The floating Northern Hemisphere (NH) 14 C data sets derived from the YD-B and Central European Lateglacial Master tree-ring series are matched against the new kauri data, forming a robust NH 14 C time series to ~14, 200 cal BP. Our results show that IntCal13 is questionable from ~12, 200–11, 900 cal BP and the ~10, 400 BP 14 C plateau is approximately 5 decades too short. The new kauri record and repositioned NH pine 14 C series offer a refinement of the international 14 C calibration curves IntCal13 and SHCal13, providing increased confidence in the correlation of global paleorecords.